PENGARUH PENGGUNAAN TUNGGAL MAUPUN KOMBINASI BIGUANID DAN PROTON PUMP INHIBITOR TERHADAP NEUROPATI DIABETIK STUDI KADAR VITAMIN B12 SERUM PADA PENDERITA DIABETES MELITUS TIPE 2 - Marliani Afriastuti,* Aris Catur Bintoro,* Dwi Pudjonarko,* Tjokorda Gde Dalem Pemayun** (Neurona Majalah Kedokteran Neuro Sains, 2017)
INTRODUCTION DIABETIC NEUROPATHY IS A NEUROLOGIC DISORDER THAT RELATED TO DIABETES MELLITUS IT CAN BE FOUND IN 2550 TYPE 1 AND TYPE 2 DIABETES MELLITUS BIGUANID METFORMIN AND PROTON PUMP INHIBITOR PPI FREQUENTLY REPORTED AS A PHARMACOLOGICAL CAUSE OF VITAMIN B12 DEFICIENCY VITAMIN B12 DEFICIENCY MAY WORSEN DIABETIC NEUROPATHY THAT ALREADY OCCURED ALSO MAY ACCELERATE DIABETIC NEUROPATHY EVENTS